Women's cellphone access and ownership in rural Uganda: implications for self-care interventions - Willow Leahy; Maryam Abomoslim; Amy Booth; Anna Gottschlich; Nelly Mwandacha; Hallie Dau; Priscilla Naguti; Beth Payne; Laurie Smith; Carolyn Nakisige; Gina Ogilvie (BMC, 2024)
Abstract Background The World Health Organization (WHO) call for cervical cancer elimination includes increasing global cervical screening coverage. HPV-based self-collection (HPV-SC) is a promising screening model for low- and middle-income countries (LMICs), and while digital technology, such as cellphones, can be used to streamline HPV-SC, there is limited data on digital technology penetration in LMICs. Determining women's cellphone access is critical to understanding the feasibility of using cellphones to support HPV-SC. Methods This study is a secondary analysis of a larger clinical trial. Participants of a cluster-randomized trial comparing HPV-SC models in Uganda completed a survey, including questions about demographics, cellphone access/ownership, prior cervical cancer screening (CCS), and willingness to receive CCS information by text. A logistic regression model was used to determine adjusted rates of cellphone ownership using survey variables as factors. Results Of 2019 participants, 76.1% owned a cellphone. In non-cellphone owners (n = 483), 82.4% had daily cellphone access and 7.3% had no access. Compared to non-cellphone owners, cellphone owners were significantly older, more educated, closer to major health centers, more likely to have prior CCS, and more willing to receive a CCS text. In the logistic regression model, the aforementioned variables were all significantly associated with the odds of owning a cellphone. Conclusions As health care systems consider adopting HPV-SC, it is imperative to understand digital technology penetration. The majority of participants were cellphone owners and were willing to receive CCS information by text; however, significant socioeconomic and demographic differences remain between cellphone owners and non-owners. Further investigation is needed to understand whether HPV-SC using cellphones is feasible in similar settings. Trial registration ISRCTN, 12767014 . ClinicalTrials.gov, NCT04000503 .